2016
DOI: 10.1093/asj/sjw061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Body Image and Sexual Satisfaction in Women Undergoing Female Genital Plastic/Cosmetic Surgery

Abstract: Abstract:Background: Little prospective data exists regarding the procedures constituting female genital plastic/cosmetic surgery (FGPS).Objectives: To evaluate whether the procedures of labiaplasty and vaginoperineoplasty improve genital self-image image, and evaluate effects on sexual satisfaction.Method: Prospective cohort case-controlled study of 120 subjects evaluated at baseline, 6, 12, and 24 months postoperative, paired with a demographically similar control group. Interventions include labiaplasty, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 42 publications
3
47
0
Order By: Relevance
“…Our position, though unorthodox, is not entirely without support. We note that we are not alone in suggesting unreflective and entrenched positions may need rethinking (Veal et al 2014;Goldstein and Jutrzonka 2016;Goodman et al 2016).…”
Section: Unreflective and Entrenched Positionsmentioning
confidence: 78%
See 2 more Smart Citations
“…Our position, though unorthodox, is not entirely without support. We note that we are not alone in suggesting unreflective and entrenched positions may need rethinking (Veal et al 2014;Goldstein and Jutrzonka 2016;Goodman et al 2016).…”
Section: Unreflective and Entrenched Positionsmentioning
confidence: 78%
“…This contributes to the entrenching of unreflective positions mentioned above. We are not alone in noting the lack of evidence underpinning policy documents and unreflective positions: "[a]uthors, even those with impeccable academic credentials, have displayed bias in their editorial and position statements" (Goodman et al 2016;Goodman 2017, 335).…”
Section: Current Policy and Clinical Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study demonstrated a signi cant improvement in body image 6 months after surgery. Similarly, another study found better body image and sexual satisfaction after surgical intervention [36,50]. The patient may consider the altered genital anatomy due to the surgery to have a signi cant impact on their general sense of attractiveness.…”
Section: Discussionmentioning
confidence: 91%
“…Most labiaplasty studies reported that different techniques appear to offer excellent and equally similar esthetic results with high patient satisfaction and very low complication rates [1]. In addition, using validated symptom questionnaires in some studies, significant improvements in sexual satisfaction, pain during intercourse, and psychological state were found in patients after genital cosmetic surgery [2]. However, most such data lacks strong scientific evidence and are reported by esthetic surgeons without any urogynecological assessment.…”
Section: The Goodmentioning
confidence: 99%